Estimation of The Efficiency of Different Academic Departments Using Data Envelopment Analysis: A Study in an Iranian Medical University - Roohollah askari (Journal of Medical Education and Development, 2019)
Abstract Introduction: In every country, educational systems are regarded as the axes of development. Therefore, evaluating different academic departments as the main parts of educational systems is one of the most important responsibilities for university managers and authorities This study aimed at evaluating educational performance of all departments at the School of Health, a University of Medical Sciences using Data Envelopment Analysis technique in a time period of 2012-2015. Methods: This descriptive, cross-sectional study evaluated the performance of the School of Health departments from 2012 to 2015 using Data Envelopment Analysis technique and Deap version 2.1. Results: The study findings revealed that 57% of the academic departments were efficient and had constant returns to scale (CRS) while others (43%) had decreasing returns to scale (DRS). The Departments of Health Care Management, Nutrition, and Environmental Health were mentioned as reference groups for those inefficient ones. Conclusion: Improving the quality of universities' performance depends greatly on competent and well-organized academic departments. Thus inefficient departments should benchmark reference groups to increase their output and promote the performance. Keywords: Performance evaluation, DEA, Academic department, Efficiency.